Best Responding to What? A Behavioral Approach to One Shot Play in 2x2 Games - Andrea Gallice (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
We introduce a simple procedure to be used for selecting the strategies most likely to be played by inexperienced agents who interact in one shot 2x2 games. We start with an axiomatic description of a function that may capture players' beliefs. Various proposals connected with the concept of mixed strategy Nash equilibrium do not match this description. On the other hand minimax regret obeys all the axioms. Therefore we use minimax regret to approximate players' beliefs and we let players best respond to these conjectured beliefs. When compared with existing experimental evidences about one shot matching pennies games, this procedure correctly indicates the choices of the vast majority of the players. Applications to other classes of games are also explored.
urn:nbn:de:bvb:19-epub-1365-2
Keywords: C72; C91; 330; prediction; beliefs; mixed strategy Nash equilibrium; minimax regret; matching pennies; experiments.